A SKRINING VIRTUAL BERBASIS LIGAN SENYAWA PRODUK NATURAL TERHADAP SARS-COV-2 MAIN PROTEASE (Mpro) MENGGUNAKAN PENDEKATAN SIMILARITAS SUBSTRUKTUR DAN PEMBELAJARAN MESIN - GP. Wahyunanda Crista Yuda (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2022)
Introduction: Increased ROS (reactive oxygen species) and SASP (senescence-associated secretory phenotype) lead to skin aging via cellular senescence. CD36 (Cluster Difference 36) is found overexpressed in senescent cells and accepts various activators that generate ROS and SASP. Cinnamon (Cinnamomum zeylanicum) has been known to exert several pharmacological effects like antioxidant and anti-senescence. However, its anti-senescence effect on CD36 has not been reported yet. This study aims to prove that cinnamon’s compounds are effective to inhibit CD36 in order to stop skin aging caused by senescence. Methods: Literature studies and in silico approaches such as database searching, molecular docking, and KNIME open analytic platform were used in this study. Result: Cinnamaldehyde is proven as a better competitive CD36 inhibitor (DICE Score: 0,886; Tanimoto Score: 0,939) with better affinity than native ligand and previously studied inhibitors (RMSD: 0,74 Å; S: -7,43 kcal/mol). Bioinformatics investigations also showed that major compounds of cinnamon target CD36 regulator, oxidoreductases, and SASP-producing receptors that co-expressed with CD36. Conclusion: Active components of cinnamon are potential to be an anti skin aging by inhibiting CD36, regulating CD36, and eradicating senescent factors.